Moving toward a learned profession and purposeful integration: Quantifying the gap between the academic and practice communities in auditing and identifying new research opportunities. Issue 1 (19th November 2015) - Ratzinger-Sakel, Nicole V.S.; Gray, Glen L.
Abstract : The Pathways Commission on Accounting Higher Education Report (2012) recommends turning the accounting profession into a learned profession through the purposeful integration of accounting research, education and practice. This paper develops an approach to identifying and quantifying the specific dimensions of the gap between the accounting academic and practice communities, thereby contributing to moving the accounting profession to a learned profession. For this we focus on audit research, because the discussion of the perceived gap between audit research and audit practice is extensive; yet no one has actually quantified that gap to date. While researchers have classified and quantified audit research, no one has done likewise for publications issued by the practice community. We choose the 38 distinct recommendations in the Advisory Committee on the Auditing Profession (ACAP) Final Report as an initial benchmark. We compare those recommendations to the 16 audit research themes from Lesage and Wechtler (2012) and to the publications spanning 33 years of audit research posted on the American Accounting Association website. Eight Lesage and Wechtler themes, comprising 50% of the themes, were not explicitly included in any ACAP distinct recommendation. Conversely, seven distinct recommendations had zero direct matches in the audit literature. This gap suggests future research opportunities in terms of exploring underrepresented topics and, maybe more importantly, the reasons why some topics are underrepresented.